An indirect ELISA for the detection of antibodies against Dirofilaria spp. in cats - Lívia Perles; Mariaelisa Carbonara; Jairo Alfonso Mendoza-Roldan; Luigi Venco; Simona Gabrielli; Domenico Otranto (Parasites & Vectors, 2025)
Abstract Background Dirofilaria immitis and D. repens are mosquito-borne filaroids that primarily infect dogs but also cats. Diagnosing feline dirofilariosis is challenging because of the low parasitic burdens and transient or absent microfilaremia. To improve detection of antibodies against Dirofilaria spp. in cats, an indirect enzyme-linked immunosorbent assay (ELISA) using somatic antigens of D. immitis was standardized. Methods Serum samples from cats positive for D. immitis, D. repens, bronchopulmonary metastrongylids and gastrointestinal helminths as well as negative sera were tested to evaluate the sensitivity (Se) and specificity (Sp). Three different antigen concentrations (2, 3 and 4 μg/ml) and two concentrations of horseradish peroxidase (HRP) IgG anti-cat conjugate (1:10,000 and 1:20,000) were used to screen the optimal titration of the test. Once the best conditions were established, Se and Sp were assessed by testing 151 serum samples positive for D. immitis, D. repens and other parasites (i.e. feline lungworms, gastrointestinal helminths) or negative. Results The optimized ELISA showed 89% Se and 98% Sp in detecting D. immitis infections, presenting a cross-reactivity with D. repens. A cut-off point of 1.150 was established to classify positive and negative samples. Conclusions The developed ELISA may improve the detection of antibodies against Dirofilaria spp. in cats, also in epidemiological contexts characterized by multiple helminth infections. Future efforts will focus on reducing the cross-reactivity with D. repens, therefore increasing ELISA Sp. Graphical Abstract